Tackling undeclared work in the European Union: An evaluation of government policy approaches - Colin C. Williams (UTMS Journal of Economics, 2019)
In recent years, it has been increasingly recognised that governments seeking to tackle undeclared work effectively should adopt a holistic approach. This seeks to coordinate strategy across the fields of labour, tax and social security law, and to use the full range of policy measures available. The aim of this paper is to evaluate the extent to which European Union member states adopt such an integrated holistic approach when tackling undeclared work by coordinating strategy across the fields of labour, tax and social security law, and using the full range of policy measures available. Reporting a 2017 survey of the official representatives of the national governments on the European Commission's European Platform Tackling Undeclared Work, the finding is that most national governments continue to adopt an uncoordinated fragmented approach to strategy and use only a limited range of mostly deterrent policy measures. The paper concludes by discussing how a more holistic approach could be achieved across EU member states.
Keywords: H26; J46; K42; O17; P37; 330; informal economy; tax evasion; public policy; European Union